Fruquintinib in Combination With PD-1 Inhibitors in Patients With Refractory Non-MSI-H/pMMR Metastatic Colorectal Cancer: A Real-World Study in China - Gou, Miaomiao; Qian, Niansong; Zhang, Yong; Yan, Huan; Si, Haiyan; Wang, Zhikuan; Dai, Guanghai (Frontiers in Oncology, 2022)
Background Fruquintinib, a vascular endothelial growth factor receptor inhibitor, is a new anticancer drug independently developed in China to treat refractory metastatic colorectal cancer (mCRC). In Japan, regorafenib combined with nivolumab has been demonstrated to be promising in patients with refractory mCRC. Here, in a real-world study, we were aimed to evaluate the efficacy of fruquintinib with various programmed death-1 (PD-1) inhibitors after standard treatment in Chinese non-microsatellite instability-high (MSI-H)/mismatch repair proficient mCRC patients. Methods A total of 45 patients with refractory mCRC were involved in the study. They received fruquintinib (3 or 5 mg, orally administered once a day for 3 weeks followed by 1 week off in 4-week cycles) and a PD-1 inhibitor(200 mg pembrolizumab, 3 mg/kg nivolumab, 200 mg sintilimab or camrelizumab, intravenously administered on D1 once every 3 weeks). Progression-free survival (PFS), overall survival (OS), disease control rate (DCR), and objective response rate (ORR) were reviewed and evaluated. Results Among the 45 patients, the median age was 54 years (29-85). The ORR was 11.1% (5/45), DCR 62.2% (28/45), median PFS equal 3.8 months, and median OS was 14.9 months. The response duration was 3.4 months. PFS between left and right primary tumors and PFS with or without lung metastases were both not significantly different (p > 0.05), which was inconsistent with the result of REGONIVO study. The multivariate analysis indicated no association of OS benefit in the specified subgroups. No adverse-effect-related deaths were reported. Conclusions Fruquintinib, in combination with anti-PD-1, was observed to have clinical activity in a small population of patients with heavily pretreated mCRC in our center. Further studies are needed to verify this outcome in a large population.